Effects of six weeks of medicine ball training on throwing velocity, throwing precision, and isokinetic strength of shoulder rotators in female handball players - Raeder, C.; Fernandez-Fernandez, J.; Ferrauti, A. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to investigate the effects of 6 weeks of medicine ball training (MBT) on throwing velocity, throwing precision, and isokinetic strength of shoulder rotators in competitive female handball players. Twenty-eight players (mean ± SD; age: 20.8 ± 3.3 years, height: 170.5 ± 5.6 cm, body mass: 65.2 ± 8.0 kg) were randomly assigned to an MBT group (TG; n = 15) and a control group (CG; n = 13). TG performed a supervised MBT program, 3 times a week for a total of 6 weeks, focusing on handball-specific movement patterns. Both groups, TG and CG, also conducted a supervised shoulder injury prevention program with elastic tubes, as part of the warm-up, finishing with regular handball throws. Results showed a significant group × time interaction in throwing velocity (p < 0.001) with the TG posttest results being significantly higher compared with CG (d = 2.1), and also a significant main time effect (p < 0.001), with an increase in throwing velocity of 14% (d = 3.0) and 3.7% (d = 0.3) for both TG and CG, respectively. Throwing precision did not significantly differ between groups and time points. Isokinetic strength measures revealed a significant group × time interaction (p = 0.05) with the TG posttest results being significantly higher compared with CG (d = 0.9) and also a significant main time effect (p < 0.01) with an increase of 15% (d = 0.9) in concentric shoulder internal rotation at 180°/s in the dominant arm in TG, whereas no significant changes occurred in CG. The present results indicate that 6 weeks of MBT elicit significant improvements in functional performance (i.e., throwing velocity) in female handball players, whereas throwing precision remained unaffected. Medicine ball training exercises seem to be a useful and inexpensive strength training strategy in enhancing functional performance by closely mimicking sport-specific movement activities.